Ultrasound versus MRI: is there a difference in measurements of the fetal lateral ventricles?. (1st February 2017) - Behrendt, Nicholas; Zaretsky, Michael V.; West, Nancy A.; Galan, Henry L.; Crombleholme, Timothy M.; Meyers, Mariana L.
Abstract: Objective : To evaluate whether fetal brain lateral ventricle measurements differ between ultrasound (US) and MRI. Methods : We evaluated 115 fetuses with US and MRI performed within 24 h of each other. Ventricular measurements were performed in the axial plane at the level of the atria for both modalities and the right and left ventricles were evaluated separately. We compared mean measurements; mean differences, association with gestational age (GA), association with the presence of a brain anomaly, and agreement between MRI and US. Results : The LV and RV were measured in 65 and 64 cases, respectively. LV and RV size estimates were significantly greater when measured by MRI compared with US ( p < 0.001). Therefore, LV and RV were 0.87 mm and 0.89 mm larger in MRI versus US, respectively. Neither GA at measurement or presence/absence of a brain anomaly was significantly associated with differences in measurements. When comparing the agreement between the US and MRI measurements for ventriculomegaly; the kappa level of agreement for the LV and RV was 0.74 for each. Conclusion : MRI measurements of ventricles are significantly larger than the measurements by US by ∼1 mm. There is a good level of agreement when categorizing by normal, mild and severe ventriculomegaly.